1992
DOI: 10.2337/diacare.15.5.626
|View full text |Cite
|
Sign up to set email alerts
|

Early Infant Diet and Risk of IDDM in Blacks and Whites: A Matched Case-Control Study

Abstract: The analyses of this study cohort suggest that the observed protective effect of breast-feeding on the risk of IDDM may be related to differences in the age at exposure to breast milk substitutes in blacks but not in whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
6

Year Published

1994
1994
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 0 publications
0
40
0
6
Order By: Relevance
“…The results suggest that young age at introduction of dairy products and high milk consumption during childhood increase the levels of cow's milk antibodies and that high IgA antibodies to cow's milk formula are independently associated with increased risk of IDDM. [Diabetologia (1994) 37: 381-387] early introduction of dairy products or other foods could be related to an increased risk of IDDM [3][4][5][6][7]. A detailed study of infant feeding patterns indicated that the age at introduction of dairy products had the closest association with the risk of IDDM when the duration of both overall and exclusive breast-feeding was taken into account [8].…”
mentioning
confidence: 99%
“…The results suggest that young age at introduction of dairy products and high milk consumption during childhood increase the levels of cow's milk antibodies and that high IgA antibodies to cow's milk formula are independently associated with increased risk of IDDM. [Diabetologia (1994) 37: 381-387] early introduction of dairy products or other foods could be related to an increased risk of IDDM [3][4][5][6][7]. A detailed study of infant feeding patterns indicated that the age at introduction of dairy products had the closest association with the risk of IDDM when the duration of both overall and exclusive breast-feeding was taken into account [8].…”
mentioning
confidence: 99%
“…The higher abundance of transporter mRNA indicates a potential for increased nutrient uptake from the intestine at this "critical" time, suggested by this study to be from 44 days of age, at which time the pups may begin consuming the dams' diet through to 21 days of age when weaning occurs. In human infants, many retrospective studies have shown a negative correlation between breast feeding as an infant and IDDM occurrence in adolescence [32,33]. Breast feeding may confer protection by decreasing exposure to foreign antigens via solid food or formula.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] A number of earlier hypotheses with some supporting evidence have been put forward to explain the possible mechanism of action of the environmental trigger including b-cell death secondary to virally triggered inflammation, molecular mimicry, superantigens and diet. [10][11][12][13][14][15][16][17][18][19] What is certain is that at some point postnatally, the immune system of a genetically predisposed individual is activated to infiltrate chronically the islets of Langerhans. While the initial phase of infiltration may not involve b-cell destruction, a number of studies in vivo and in vitro suggest that immune cells become able to render b-cells dysfunctional through the actions of cytokines they produce such as interleukin-1b.…”
Section: Type I Diabetes Mellitus: the Autoimmune Processmentioning
confidence: 99%